2022
DOI: 10.3390/healthcare10061065
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Telemedicine on Parkinson’s Care during the COVID-19 Pandemic: An Italian Online Survey

Abstract: Traditionally, medical care and research in Parkinson’s disease (PD) have been conducted through in-person visit. The recent Coronavirus Disease 2019 (COVID-19) pandemic has profoundly impacted the delivery of in-person clinical care. We conducted an online survey to investigate the impact of COVID-19 on access to telehealth care, interviewing both PD patients and neurologists. Survey responses were collected from 1 March to 31 May 2021 through an anonymous, self-reported questionnaire, on the ‘Qualtrics’ plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although telemedicine services are not superior to the in-person visits in providing care, a growing body of evidence suggests that it offers greater efficiency and service for PD patients [ 50 ]. An online survey in Italy has investigated the impact of COVID-19 on access to telehealth care among 197 PD patients and 42 neurologists [ 51 ]. The results showed that 37.6% of PD patients and 88.1% of neurologists had chosen alternatives to in-person visits, while 13.7% of PD patients and 40.5% of neurologists used telemedicine.…”
Section: Covid-19 and Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although telemedicine services are not superior to the in-person visits in providing care, a growing body of evidence suggests that it offers greater efficiency and service for PD patients [ 50 ]. An online survey in Italy has investigated the impact of COVID-19 on access to telehealth care among 197 PD patients and 42 neurologists [ 51 ]. The results showed that 37.6% of PD patients and 88.1% of neurologists had chosen alternatives to in-person visits, while 13.7% of PD patients and 40.5% of neurologists used telemedicine.…”
Section: Covid-19 and Pdmentioning
confidence: 99%
“…The results showed that 37.6% of PD patients and 88.1% of neurologists had chosen alternatives to in-person visits, while 13.7% of PD patients and 40.5% of neurologists used telemedicine. Most of them were satisfied with the use of telemedicine during the COVID-19 pandemic, indicating that telemedicine has the potential to improve the care for PD patients, especially when access to in-person visits is limited [ 51 ]. Another survey of 417 PD patients in Canada aiming to see the effects of confinement on patients’ daily living and disease management suggested that COVID-19-related confinement affected PD manifestation and management [ 52 ], and the patients reported varying levels of interest in continuing remote care via phone or video conference [ 52 ].…”
Section: Covid-19 and Pdmentioning
confidence: 99%
“…Although not superior to in-person visits, a growing body of evidence suggests that telemedicine services offer greater efficiency for PD patients [ 26 ]. An online survey in Italy has investigated the impact of COVID-19 on the access to telehealth care among 197 PD patients and 42 neurologists [ 27 ]. The results showed that 37.6% of PD patients and 88.1% of neurologists had chosen alternatives to in-person visits, while 13.7% of PD patients and 40.5% of neurologists used telemedicine services.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 32 Although usage drastically increased up to >90% in the United States, 8 , 11 , 12 , 33 , 34 implementation in Europe is lagging behind. Less than 15% of PwP in Italy 35 and Germany 9 , 36 were acquainted with video‐based consultations and less than two‐thirds of neurologists offered these services. 3 , 35 In contrast, ~50% of PwP in Germany 9 express demand for teleconsultations, with rising numbers over the development of the pandemic, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%